2021
DOI: 10.1002/bse.2733
|View full text |Cite
|
Sign up to set email alerts
|

Green bonds, sustainable development and environmental policy in the European Union carbon market

Abstract: This study assesses the non-linear effects of green bonds, conventional bonds and energy commodities on the behaviour of the cap-and-trade European Union carbon market (European Union Emissions Trading System [EU-ETS]). By estimating four models, using Markov-switching (MS) econometric methodology, non-linearities are confirmed in dynamic behaviours, observing in the global calculation a positive effect of green bonds (S&P Green and Sol Green) on the carbon market, in regimes of both high and low volatility, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(25 citation statements)
references
References 97 publications
0
24
0
1
Order By: Relevance
“…The energy transformation requires banking institutions to fundamentally change the way they operate, and thus time needed to implement a new strategy for their lending policy. It means expansion of a green loans offer, as well as their support in organizing a green bonds issue [31,92]. Taking into account the objective that Europe, which is to become the first continent to achieve net zero greenhouse gas emissions in 2050 [93], a change in the pace of green lending transformation in Polish banks must also take place.…”
Section: Results From the Survey Research (Stage 1)mentioning
confidence: 99%
See 2 more Smart Citations
“…The energy transformation requires banking institutions to fundamentally change the way they operate, and thus time needed to implement a new strategy for their lending policy. It means expansion of a green loans offer, as well as their support in organizing a green bonds issue [31,92]. Taking into account the objective that Europe, which is to become the first continent to achieve net zero greenhouse gas emissions in 2050 [93], a change in the pace of green lending transformation in Polish banks must also take place.…”
Section: Results From the Survey Research (Stage 1)mentioning
confidence: 99%
“…Empirical studies have also indicated that the main channel of "green" financing is a bank loan, which is more competitive than traditional credit products. Commercial banks in Poland, supporting the energy transformation, also mediate in the procedure of bond issues, including green bonds, or joining public-private partnerships [31]. As far as possible, it also seems that banks will expand their offer of "green" financing, as long as the pandemic crisis does not permanently affect their financial stability and the financial condition of capital recipients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…“Green bonds are bonds with a defined use of proceeds toward mitigating and adapting to climate change and solving environmental problems.” (Deng et al, 2020, p.57). Previous studies examine various aspects of a green bond, such as determinants of the offer size and issuance of a green bond (Barua & Chiesa, 2019; Russo et al, 2021), whether a green bond is a different class asset (Ferrer et al, 2021), reasons behind the popularity of green bonds (Cao et al, 2021), and the effectiveness of green bonds in reducing pollution (Fatica & Panzica, 2021; Leitao et al, 2021). Elettra and Rossella (2019) explain the green bond yield premium (greenium)—the difference between yields on a conventional bond and a green bond with the same characteristics.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Leitao et al analyzed the overall topological characteristics of the global oil international trade network and the evolution of the network structure and used random matrix theory to analyze the complex spatio-temporal dynamics from the national level. e evolution of market adaptability of international oil trade is analyzed from the perspective of demand side [8]. A complex network approach was used to construct the unweighted and weighted complex networks for the 2010 gas trade.…”
Section: Related Workmentioning
confidence: 99%